الطعن بالاستئناف في المادة الادارية - مرهون عنتر (جامعة المسيلة, 2025)
This study explores the appeal process in administrative litigation, focusing on appellate review as a legal mechanism to reassess decisions issued by first-instance administrative courts. The administrative appeal serves the principle of legality and aims to protect litigants' rights by correcting potential judicial errors. The research highlights the conditions of admissibility, legal effects of appeal, and the scope of review by higher administrative courts. Selected judicial precedents are also analyzed to clarify practical applications.
Keywords: Appeal; Administrative Judiciary; Judicial Review; Legality; Annulment Action; Administrative Court; Council of State.